A study of acoustic emission testing on galvanized iron MIG welding - Afham Bazli, Razali (2012)
This thesis was carried out to investigate the characteristic of Acoustic Emission signal on galvanized iron MIG welding. The welding joint will be test as a load and there will be a few points of welding joint to be monitoring. For the study AE signal on galvanized iron, all time domain parameter (hit, count, amplitude, and frequency by Fast Fourier Transform) of signal will be observe and process with the aid of Matlab software. The data was taken by the specimen tight at the edge of the table by using clamp. The sensor located at the point and after that the load was applied to enhance the signal of Acoustic Emission. All parameter compared with different points of welding joints. The result obtain will be analyse by using Matlab and then can proceed for analysis. For result by using FFT, the signal pattern can be distinguish between non-defect welding joint and defect welding joint due to the frequency range show a different between them. For the amplitude and count, the average value of defect welding joint shows that it has higher value compare to non-defect welding joint. There are some signals that influence by disturbance noise. Hence, the signal pattern obtain could not be analyse. The factor that influence the signal or disturbance signal is noise around the test run, emission from electric surrounding and from people talking.